MANAJEMEN PRODUKSI PRODUK MAKANAN ”ROLLIE SNACK” (STUDI KASUS UMKM CEMILAN KITA DI KOTA MAKASSAR) - Nurliani Nurliani; Nur Alfiani Has; St. Sabahannur; Sitti Rahbiah (Program Studi Agribisnis Fakultas Pertanian, 2025)
Production management is an activity to organize and coordinate the use of human resources, tools and materials, effectively and efficiently to create and increase the usefulness of a good or service. The phenomenon of entrepreneurial development, now many entrepreneurs choose the culinary business compared to other businesses because humans need food ingredients at all times. Spring roll skin is a thin sheet made from wheat flour, water, salt and eggs. Rollie Snack is a food ingredient made from spring roll skin. Rollie Snack has product characteristics with a sweet and spicy taste, on the outside it has a crispy and soft texture. The purpose of this study is to describe the production process of Rollie Snack, identify product variants, prices, sales volume of Rollie Snack and analyze management functions (planning, organizing, implementing, and controlling). Rollie Snack business activities are centered in a production house in Panakkukang District, Makassar City, South Sulawesi. This business activity has been going on for 2 (two) years. The results of the study show that the Snacks MSME has implemented production management according to the business plan. The production process goes through several stages, namely forming spring roll skins, drying the skins, frying, making chocolate, vanilla, green tea, and spicy lime leaf flavor variants and mixing spring roll skins with flavor variants. Finally, it produces